2001
DOI: 10.1126/science.1057179
|View full text |Cite
|
Sign up to set email alerts
|

Dyslexia: Cultural Diversity and Biological Unity

Abstract: The recognition of dyslexia as a neurodevelopmental disorder has been hampered by the belief that it is not a specific diagnostic entity because it has variable and culture-specific manifestations. In line with this belief, we found that Italian dyslexics, using a shallow orthography which facilitates reading, performed better on reading tasks than did English and French dyslexics. However, all dyslexics were equally impaired relative to their controls on reading and phonological tasks. Positron emission tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
481
4
14

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 892 publications
(545 citation statements)
references
References 19 publications
43
481
4
14
Order By: Relevance
“…The hypothesis that the core phonological deficit in dyslexia is manifested in dysfunctional phonological processes receives support from the finding that reading difficulties and related phonological deficits persist across development, even in people with dyslexia who have compensated for their reading difficulties (Bruck, 1990(Bruck, , 1992(Bruck, , 1993Hatcher, Snowling, & Griffiths, 2002;Pennington, Orden, Smith, Green, & Haith, 1990). Such findings apply equally to adults with dyslexia who read in transparent languages (Paulesu et al, 2001).…”
Section: Dyslexia Across the Life-spanmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that the core phonological deficit in dyslexia is manifested in dysfunctional phonological processes receives support from the finding that reading difficulties and related phonological deficits persist across development, even in people with dyslexia who have compensated for their reading difficulties (Bruck, 1990(Bruck, , 1992(Bruck, , 1993Hatcher, Snowling, & Griffiths, 2002;Pennington, Orden, Smith, Green, & Haith, 1990). Such findings apply equally to adults with dyslexia who read in transparent languages (Paulesu et al, 2001).…”
Section: Dyslexia Across the Life-spanmentioning
confidence: 99%
“…In English, the diagnosis of dyslexia proceeds on the basis of a discrepancy between reading accuracy and age (or in some cases IQ). The same criteria cannot be used in transparent writing systems where accuracy levels are typically high (Paulesu et al, 2001). Rather, criteria tend to center on speed and fluency rather than error-rate.…”
Section: Dyslexia In Different Languagesmentioning
confidence: 99%
“…For example, many fMRI studies have reported abnormal BOLD signals in the dyslexic brain; most often the temporoparietal cortex involved in phonological processes, and the ventral occipito-temporal cortex (often referred to as the visual word form area, or VWFA) involved in representing the visual forms of words (e.g., Brunswick, McCrory, Price, Frith, & Frith, 1999;Kronbichler et al, 2006;Paulesu et al, 2001;Rumsey, Nace, & Donohue, 1997;Shaywitz et al, 2007). Abnormal activation in either of these areas has been used to support the claim that phonological deficits are responsible for the dyslexia.…”
Section: Practical Problemsmentioning
confidence: 99%
“…However, a better understanding of the impact of orthographic depth on the underlying brain networks would be of particular interest since the consistency of grapheme/phoneme correspondences has been shown to critically influence literacy acquisition (e.g. Ellis & Hooper, 2001;Goswami, 1998;Lallier, Carreiras, Tainturier, Savill, & Thierry, 2013), reading performance (Seymour, Aro, & Erskine, 2003) and the emergence of languagerelated disorders such as dyslexia (Goswami, 1998;Paulesu et al, 2001;Wheat, Cornelissen, Frost, & Hansen, 2010).…”
Section: Introductionmentioning
confidence: 99%